A CURRICULUM ANALYSIS AND INTEGRATION OF CHEMICAL ENGINEERING EDUCATION - Jotanović, M.; Tadić, G. (Journal of Engineering & Processing Management, 2009)
Most commonly, all reforms of curriculum and study programmes in the educational system of Chemical Engineering are based on knowledge integration and developing tools which are designed to help students acquire a global picture of their professional calling. Therefore, this reform, which is the most comprehensive so far, and which was caused by the implementation of the Bologna model as well as by the small number of students at technical faculties, has a major significance for all the faculties of Chemical Engineering. This study, apart from presenting the factors which affect the development of studies in this area, gives a thorough review of the past and the existing educational systems at the faculties of Chemical Engineering in Europe. Thus the implementation of the Bologna model is used in order to harmonize curricula in the educational system of Chemical Engineering in Europe through defined goals of knowledge acquisition and a basic curriculum with the topics that should be incorporated in the curriculums of all the faculties of Chemical Engineering.